HYPOGLYCEMIC EFFECT OF HIGH-RESISTANT STARCH ANALOG RICE THROUGH GLP-1 AND INSULIN OR HIGH-RESISTANT STARCH ANALOG RICE ATTENUATES BLOOD GLUCOSE LEVEL THROUGH ENHANCEMENT OF GLP-1 AND INSULIN - HAIRRUDIN; SOETJIPTO; RETNO HANDAJANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was to investigate the effect of analog rice (AR) on glucagon-like peptide-1 (GLP-1) and insulin serum levels, glucose transporter-2 (GLUT-2) expression, and fasting blood glucose (FBG) level in diabetic rats. Methods: Fifty male Wistar rats divided into the control group (n=10) and the experimental group. High-fat diet and streptozotocin were administered in experimental groups, which then divided into four equal groups (n=10, each) (negative control group, rice group, AR1 and AR2 group, given standard pellet, rice pellet, AR1 and AR2 pellet, respectively, for 6 weeks). GLP-1 and insulin serum levels were measured by enzyme-linked immunosorbent assay. The expression of GLUT-2 and the number of pancreatic β-cells observed using an immunohistochemistry method. Results: FBG levels in the AR1 and AR2 groups decreased, while the rice group remained. GLP-1 serum levels of the negative control and rice groups were not significantly different from the control group, while the AR1 and AR2 groups higher than the control group (p≤0.05). All the treatment groups had insulin serum levels significantly lower than control group (p≤0.05), except the AR1 group. The expression of GLUT-2 and the number of pancreatic β-cells in the treatment groups were less than the control group, but between treatment groups were not significantly different. Conclusion: AR significantly effective in reducing FBG level in diabetic rats through stimulation of increased GLP-1 and insulin serum levels serum levels but AR did not affect on the expression of GLUT-2.